Functional cure of a chronic virus infection by shifting the virus - host equilibrium state - Bocharov, Gennady; Grebennikov, Dmitry; Cebollada Rica, Paula; Domenjo-Vila, Eva; Casella, Valentina; Meyerhans, Andreas (Frontiers in Immunology, 2022)
The clinical handling of chronic virus infections remains a challenge. Here we describe recent progress in the understanding of virus - host interaction dynamics. Based on the systems biology concept of multi-stability and the prediction of multiplicative cooperativity between virus-specific cytotoxic T cells and neutralising antibodies, we argue for the requirements to engage multiple immune system components for functional cure strategies. Our arguments are derived from LCMV model system studies and are translated to HIV-1 infection.